p53-Independent Effects of Set7/9 Lysine Methyltransferase on Metabolism of Non-Small Cell Lung Cancer Cells - Daks, Alexandra; Shuvalov, Oleg; Fedorova, Olga; Petukhov, Alexey; Lezina, Larissa; Zharova, Arsenia; Baidyuk, Ekaterina; Khudiakov, Alexander; Barlev, Nickolai A. (Frontiers in Oncology, 2021)
Set7/9 is a lysine-specific methyltransferase which regulates the functioning of both histone and non-histone substrates thereby significantly affecting the global gene expression landscape. Using the microarray expression profiling, we have identified several key master-regulators of metabolic networks, including c-Myc, that were affected by Set7/9 status. Consistent with this observation, c-Myc transcriptional targets – genes encoding glycolytic enzymes hexokinase (HK2), aldolase (ALDOB) and lactate dehydrogenase (LDHA) were up-regulated upon Set7/9 knockdown (Set7/9KD). Importantly, we showed that shRNA-mediated attenuation of Set7/9 augmented c-Myc, GLUT1, HK2, ALDOA, and LDHA expression in non-small cell lung cancer (NSCLC) cell lines not only at the transcriptional but also at the protein level. In line with this observation, Set7/9KD significantly augmented membrane mitochondrial potential (MMP), glycolysis, respiration, and the proliferation rate of NSCLC cells. Importantly, all these effects of Set7/9 on cell metabolism were p53-independent. The bioinformatic analysis has shown a synergistic impact of Set7/9 together with either GLUT1, HIF1A, HK2, or LDHA on the survival of lung cancer patients. Based on these evidences we hypothesize that Set7/9 can be an important regulator of energy metabolism in NSCLC.